Standardizing HIPEC and perioperative care for patients with ovarian cancer in the Netherlands using a Delphi-based consensus - Ruby M. van Stein; Christianne A.R. Lok; Arend G.J. Aalbers; Ignace H.J.T. de Hingh; Aletta P.I. Houwink; Herman J. Stoevelaar; Gabe S. Sonke; Willemien J. van Driel (Gynecologic Oncology Reports, 2022)
Objective: Hyperthermic Intraperitoneal Chemotherapy (HIPEC) is standard of care in the Netherlands in patients with stage III epithelial ovarian cancer following interval cytoreductive surgery (CRS). Differences in patient selection, technical aspects, and perioperative management exist between centers performing HIPEC. Standardization aims to reduce unwanted variation in clinical practice. As part of an implementation process, we aimed to standardize perioperative care for patients treated with CRS and HIPEC using a Delphi-based consensus approach. Methods: We performed a two-phase modified Delphi method involving a multidisciplinary panel of 40 experts who completed a survey on CRS and HIPEC. During a consensus meeting, survey outcomes and available scientific evidence was discussed. Items without consensus (<75% agreement) were adjusted and evaluated in a second survey. Results: Consensus was reached in the first round on 51% of items. After two rounds, consensus was reached on the majority of items (82%) including patient selection, preoperative workup, technical aspects of CRS and HIPEC, and postoperative care. No consensus was reached on the role of HIPEC in rare ovarian cancer types, preoperative bowel preparation, timing to create bowel anastomoses, and manipulation of the perfusate. Conclusions: Dutch experts reached consensus on most items regarding interval CRS and HIPEC for ovarian cancer. This consensus study may help to align treatment protocols and to minimize practice variation. Topics without consensus may be put on the research agenda of HIPEC for ovarian cancer.